2018
DOI: 10.1016/j.bbmt.2017.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Report by the Pediatric Acute Lung Injury and Sepsis Investigators and Pediatric Blood and Marrow Transplantation Consortium Joint Working Committees on Supportive Care Guidelines for Management of Veno-Occlusive Disease in Children and Adolescents, Part 3: Focus on Cardiorespiratory Dysfunction, Infections, Liver Dysfunction, and Delirium

Abstract: Some patients with veno-occlusive disease (VOD) have multiorgan dysfunction, and multiple teams are involved in their daily care in the pediatric intensive care unit. Cardiorespiratory dysfunction is critical in these patients, requiring immediate action. The decision of whether to use a noninvasive or an invasive ventilation strategy may be difficult in the setting of mucositis or other comorbidities in patients with VOD. Similarly, monitoring of organ functions may be very challenging in these patients, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 159 publications
(170 reference statements)
1
6
0
Order By: Relevance
“…In line with our results, Mitchell et al (2017) showed that delirium in hospital had an as-sociation with all-cause one-year mortality following hip fracture in older cases with no dementia (31). Also, similar to previous studies, the other underlying factors can affect mortality rate including cancer (32), hepatic (33), renal (34), and hematologic diseases (35,36).…”
Section: Discussionsupporting
confidence: 90%
“…In line with our results, Mitchell et al (2017) showed that delirium in hospital had an as-sociation with all-cause one-year mortality following hip fracture in older cases with no dementia (31). Also, similar to previous studies, the other underlying factors can affect mortality rate including cancer (32), hepatic (33), renal (34), and hematologic diseases (35,36).…”
Section: Discussionsupporting
confidence: 90%
“…We suspect delirium would have had a significant association and high odds of psychotropic usage in thoracic organ population given the prolonged periods of time in the ICU and frequency of events that impact acute neurocognitive functioning (eg, hypotension, sepsis, hypercapnia, hypoxemia, and mechanical ventilation). 19,20 Finally, significant thoracic organ Nevertheless, there is evidence to support the combination of therapy and medication for effective treatment of anxiety in pediatric patients, 24 and 50% of SOT patients with anxiety in our sample had a lifetime psychotropic medication history. Depression, mood, and anxiety disorders are significant predictors of morbidity, mortality, and adherence in medically ill patients [25][26][27] and should be adequately treated in SOT patients in order to improve outcomes.…”
Section: Discussionmentioning
confidence: 75%
“…As standardized delirium assessment was not conducted for these patients, the association with delirium, unfortunately, could not be further evaluated in detail. We suspect delirium would have had a significant association and high odds of psychotropic usage in thoracic organ population given the prolonged periods of time in the ICU and frequency of events that impact acute neurocognitive functioning (eg, hypotension, sepsis, hypercapnia, hypoxemia, and mechanical ventilation) . Finally, significant thoracic organ psychotropic medication use may also be attributed to the higher frequency of medical decompensation while awaiting transplant and immediately post‐transplant compared to abdominal organ disease, as end‐of‐life disease progression was also a significant variable for psychotropic usage in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe VOD/SOS may develop multiorgan dysfunction and failure and require care in ICUs. It is common, in this setting, for numerous teams to be involved in the care of a critically ill patient with VOD/SOS 23. Intensivists are ultimately responsible for the care of these patients, given their expertise in cardiopulmonary and end-organ failure.…”
Section: Composition and Practices Of A Collaborative Vod/sos Teammentioning
confidence: 99%
“…Their bedside view allows them to quickly notice a change in status, to screen for delirium, and to monitor treatment effectiveness, potential discomfort, or psychosocial concerns. 20 , 22 , 23 They are poised to voice any concerns and to advocate for patients. Accurate and timely recognition of VOD/SOS is crucial for the initiation of appropriate treatment, and these nurses use the strength of support assessment for patient assessment and monitoring, the mainstay of effective nursing support.…”
Section: Composition and Practices Of A Collaborative Vod/sos Teammentioning
confidence: 99%